2007
DOI: 10.1139/y07-077
|View full text |Cite
|
Sign up to set email alerts
|

Statin treatment increases formation of carbon monoxide and bilirubin in mice: a novel mechanism of in vivo antioxidant protection

Abstract: Heme oxygenase (HO) has a central role in cellular antioxidant defences and vascular protection, and it may mediate pleiotropic actions of drugs used in cardiovascular therapy. We investigated whether long-term use of statins upregulates HO activity and increases carbon monoxide (CO) and bilirubin levels in vivo. Adult FvB mice were given atorvastatin or rosuvastatin (5 mg/kg) daily by i.p. injections for 1, 2, or 3 weeks. HO activity, tissue CO, bilirubin, and antioxidant levels, total plasma bilirubin, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 48 publications
0
55
0
1
Order By: Relevance
“…Animal studies have reported that statin administration increases heme oxygenase expression in heart and lung tissue, together with an increase in serum bilirubin level. 41,42 Increases in heme oxygenase levels in response to statins have also been identified in human endothelial tissues, 43 and studies in humans show a modest increase in serum bilirubin that is independent of changes in liver enzymes of Ϸ10% to 20% after statin treatment. 44,45 If heme oxygenase stimulation explains some the mechanism of statin efficacy, via bilirubin or other byproducts, and this stimulation is more pronounced in patients with a higher bilirubin level measured before prescription, this could also partially explain the negative relationships with CVD described in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have reported that statin administration increases heme oxygenase expression in heart and lung tissue, together with an increase in serum bilirubin level. 41,42 Increases in heme oxygenase levels in response to statins have also been identified in human endothelial tissues, 43 and studies in humans show a modest increase in serum bilirubin that is independent of changes in liver enzymes of Ϸ10% to 20% after statin treatment. 44,45 If heme oxygenase stimulation explains some the mechanism of statin efficacy, via bilirubin or other byproducts, and this stimulation is more pronounced in patients with a higher bilirubin level measured before prescription, this could also partially explain the negative relationships with CVD described in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways include those involving NO/GC, ROS and MAPKs. The relevant biosynthetic enzyme, HO, has a central role in cellular antioxidant defence and vascular protection, and it may mediate many of the actions of drugs used in cardiovascular therapy (Muchova et al, 2007). Cardiovascular tissues express HO, which metabolizes haem to form CO. Up-regulation of HO-1 occurs in the heart after stress such as I/R and provides cardioprotection; most evidence indicates that CO is responsible for most of these beneficial effects (Johnson et al, 2004;Peers and Steele, 2012), as it exerts anti-apoptotic and cytoprotective effects (Stein et al, 2012).…”
Section: Introduction: Cardioprotection and Gasotransmittersmentioning
confidence: 99%
“…It is now widely recognized that the gasotransmitters NO, along with hydrogen sulphide (H2S) and carbon monoxide (CO), are involved in a multitude of physiological functions (Caliendo et al, 2010;Szabo, 2010;Peers and Steele, 2012). In the cardiovascular system, the regulatory role of NO and H2S includes vasorelaxation, stimulation of angiogenesis and cardioprotection (Szabo, 2010;Coletta et al, 2012), and that of CO includes relaxation of coronary vascular smooth muscle and cardioprotection (Muchova et al, 2007).…”
Section: Introduction: Cardioprotection and Gasotransmittersmentioning
confidence: 99%
See 2 more Smart Citations